Predicting Role of Preoperative Computed Tomography Features on Invasiveness of Thymic Neoplasms - Kumbasar, Ulaş; Taydaş, Onur; Uysal, Serkan; Dikmen, Erkan; Yılmaz, Mustafa; Demircin, Metin; Doğan, Rıza; Arıyürek, Macit (Acta Medica, 2020)
Purpose: The anterior mediastinal masses are composed of neoplasms from many different groups, thymic epithelial tumors (TET) being the most common type. Histologic subtype, tumor stage and completeness of resection are considered to be the most important prognostic factors in thymic malignancies. The aim of this study is to evaluate the association between the preoperative CT characteristics and the histological types, mostly focusing on thymic neoplasms. Methods: Preoperative CT features and pathologic data of 40 patients who underwent surgery due to an anterior mediastinal mass were retrospectively analyzed. Patients are grouped as thymomas, thymic carcinomas and others. Results: CT characteristics such as shape, contour, necrosis, lymph node enlargement, surrounding organization, pathologic invasion pattern, internal density, presence of cystic component, pleural/pericardial effusion and calcification were compared with histologic subtypes. Among these parameters solely pathologic invasion and surrounding organization were statistically different between the groups (p<0.001 and p=0.001, respectively). Correlation between the CT and pathologic tumor sizes among histologic subtypes was also analyzed and no statistically significant difference between CT and pathologic tumor sizes was detected (p>0,05). Conclusion: According to the results of our study, CT imaging has a limited role in predicting stage and malignant potential particularly for thymic neoplasms and anterior mediastinal masses.